Paracas y Chavín: variaciones sobre un tema longevo - Kaulicke, Peter (2013)
This paper focuses on matters of interpretation of early culture contact between northern cultures and coeval southern coastalevidence in a historical perspective starting with Tello. Due to problems related to terminology and methodology combined with incomplete presentation of the data recovered from excavation these interpretations are often contradictory and unsatisfying. Recent field work in the Río Grande de Nazca valley serves to discuss problems related to chronology, culture contact and the forming of new interaction spheres.